Application Rasch Model in Determining The Validity And Reliability Of The Malaysian Armed Forces Spiritual Assessment Instrument: A Pilot Analysis - Aziz, Azlisham Abdul; Mamat, Mohd Nor; Salleh, Daud Mohamed; Abdullah, Sharifah Fadylawaty Syed; Nordin, Mohd Norazmi; Yassin, Yasni Nurul Huda Mohd; Zuki, Jamizah (CENTRAL ASIA AND THE CAUCASUS, 2022)
The objective of this pilot analysis is to validate and investigate the reliability of instruments employed to evaluate Malaysian military personnel's (MMSA-i) spiritual well-being. The instrument comprises 205 items and is distributed to 44 Muslim Malaysian Armed Forces (MAF) personnel in Selangor and Kuala Lumpur, Malaysia. This instrument was developed to measure four dimensions: i) faith appreciation; ii) worship appreciation; iii) morals appreciation; iv) appreciation of Islam in the Pledge of Allegiance MAF. In this pilot analysis, the Rasch model was utilised to test the instrument's validity and reliability. The Rasch model is used to assess both respondent and item reliability and is, therefore, more robust than relying solely on Cronbach's Alpha. Item functioning was assessed employing the Winsteps Version5.0.2.0 programme in regards to reliability and item-respondent separation, as well as the suitability and polarity of items measuring constructs and centralised residual correlation values. Additionally, it permits item abortion based on item polarity, item suitability and dependent value determination using standardised residual correlation values. As a result of failing to fulfil the screening criteria, ten items were excluded from the final analysis. The final instrument has 190 items that were intended to measure the four spiritual assessment constructs. Since this is a pilot analysis, the distribution of actual respondents can be conducted to assess all four dimensions of spiritual assessment for Muslim military members in the MAF and develop the MAF members' spiritual profile further.